NgR1 knockout increased neuronal excitability and altered seizure pattern in traumatic brain injury mice brain after PTZ-induced seizure - Jinwei Zhang; Xin Chen; Kejun Du; Zhi Zhang; Yuan Ma; Yongqin Kuang; Sixun Yu; Haifeng Shu (PLoS ONE, 2025)
The recovery process from traumatic brain injury (TBI) is significantly impeded by inhibitors such as Nogo-A, myelin associated glycoprotein, and oligodendrocyte myelin glycoprotein, which exert an impact on the regeneration and repair of neuronal axons through their binding to Nogo-66 receptor 1 (NgR1). Recent research findings have revealed that NgR1 signaling may play a pivotal role in various seizure mechanisms, including the regulation of synaptic plasticity and migration of neural precursor cells. In this study, wild type (WT) and NgR1 knockout (KO) mice were utilized to establish craniocerebral injury models, while pentylenetetrazol (PTZ) was employed to induce seizures in both groups of mice following TBI. The results revealed that NgR1 KO mice exhibited heightened levels of neuronal electrical activity, along with elevated seizure scores compared to WT controls. Immunofluorescence staining demonstrated an increase in the number of excitatory synapses (P <  0.001) and a decrease in inhibitory synaptic density (P <  0.001) in NgR1 KO mice. Furthermore, the NgR1 KO model mice also displayed an augmentation in the number of presynaptic vesicles (P <  0.001), a narrowing of the synaptic gap (P <  0.001), and an elongation of the synaptic active region (P <  0.001). Our findings have demonstrated that in the previous single cognition of NgR1 inhibition in nerve function repair following TBI, revealing the potential risks associated with inhibiting NgR1 activity in nerve function repair following TBI, and providing a new perspective for understanding the role of NgR1 in the nervous system.